Penelitian E-Government di Propinsi Jawa Barat: Kajian Pustaka Sistematis - Hediyanto, Umar Yunan Kurnia Septo (Metris: Jurnal Sains dan Teknologi, 2018)
Assessment of the implementation e-government in West Java Province has decreased, despite not having an impact on increasing the development of egovernment in Indonesia compared with other countries in the world that experienced a rating increase to 107th position in 2018. Seeing the development of e-government in West Java Province makes a necessity to improve its quality so that it can have an impact on increasing Indonesia's ranking in the top position in the future. For this reason, a state of the art mapping of e-government research is needed in West Java Province based on the results of a systematic literature review. By focusing on five main steps, namely identification of research, selection of primary studies, assessment of study quality, data extraction and monitoring, and data synthesis. In addition to the five main steps, this research will look at three aspects in the design of e-government, namely aspects of technology, people and processes. The sources used in this study are journals and proceedings of seminars taken from the Google Scholar database for five years from 2014 to 2018. The key words used in searching the Google Scholar database are "e-government", "West Java ", and" Jawa Barat ". These keywords are searched in the entire article, not just in the article title. The mapping results show that research issues related to the analysis of e-government implementation are more dominant than research issues related to the design of e-government systems. Nevertheless, in the research issue related to the analysis of e-government implementation there are still opportunities to explore the interaction of G2B and G2G. Research issues related to the design of egovernment systems are dominated by the design of technological aspects, so that research opportunities are still open in the design of human aspects and processes.